(untitled) (Impact: Journal of Transformation, 2022)
Adolescents and children are more prone to traumatic critical occurrences, especially adolescents from low-income neighbourhoods. When an adolescent witnesses a traumatic incident or event in his or her life, it will have a profound and long-lasting influence on their development. The posttraumatic growth (PTG) phenomenon explores five main areas: spiritual growth, relating to others, personal strength, new possibilities and appreciating life. PTG process was grounded in Bronfenbrenner’s ecological systems theory. The descriptive-analytic quantitative design was used to measure the PTG elements amongst adolescents aged 8 to 18 in the Kibagare informal settlement. The target population was 1000 students of St. Martins School. A multistage sampling method was conducted, and 265 participants were the sample size. A questionnaire containing the Socio-Demographic Questionnaire, the Child and Adolescent Trauma Screen tool, and the Post-Traumatic Growth Inventory children updated version was administered. Data analysis was done using IBM SPSS. The findings revealed that various PTG elements existed among adolescents, indicating spiritual possibility; (M=2.517, SD=0.742), reporting new possibilities (M=2.243, SD=0.765) among others. The study recommends greater involvement of the community, parents and family in building interventions that focus on posttraumatic growth to enable the adolescent in the informal settlement to cope with traumatic events. This can be implemented through spiritual programs offered by spiritual leaders and mental health clinics in informal settlements that use the discovery of PTG elements as a part of their interventions. In addition, teachers can support adolescents in coping with traumatic experiences by inculcating the practice of the five aspects of posttraumatic growth.